P55 Extra-corporeal membrane oxygenation (ECMO) for patients with airborne high consequence infectious disease (HCID-A): Using simulation to develop patient transfer protocols. (3rd November 2019) - Sen, Ashwin Delmonte; Prower, Emma; Price, Nicholas M; Ceesay, Yusupha; Laws-Chapman, Colette; Meadows, Christopher IS
Abstract : Introduction: Currently available HCID-A patient transfer guidelines do not include reference to managing mobile ECMO support for severe respiratory failure¹. ECMO significantly increases the complexity of transfer in critically ill patients, whilst HCID-A pathogens present a novel UK risk. Guys and St Thomas' NHS Trust (GSTT) is the newly commissioned national network lead for HCID-A, and an established ECMO centre. Our team recognised the requirement for development of new guidance to ensure safe transfer of critically ill HCID-A patients, including those requiring ECMO, without compromising quality of care or safety of staff and the general public. Methods: We developed a prototype patient transfer procedure for a critically ill HCID-A patient, based on existing protocols for Ebola and mobile ECMO. This was then evaluated using an in situ simulation to test protocol performance and look for latent threats². A detailed plan and timetable were disseminated to the extensive multi-disciplinary team (MDT) involved; including intensive care, infectious diseases, infection control, emergency department, site managers, security and CT radiographers. We also undertook prior training in HCID-A personal protective equipment (PPE). The simulation was initiated by text message alert along GSTT major incident activation lines, leading to the teams gathering for a briefing. A patient simulator was transferred from ambulance, through CT scanning and then to the intensive care isolation facility. Simulation took place in 'real time' and, following its completion, there was a hot debrief of the entire MDT. Audio-visual and qualitative data were recorded throughout. Results: Learning points from the simulation and debrief were incorporated into an HCID-A standard operating procedure (SOP) for GSTT. These included the safest transfer route through the hospital (minimising impact on the emergency department), methods for lift and corridor 'lockdown', clarity on team size and responsibilities, and development of a CT scan guideline. In addition, we were able to evaluate the safety and usability of our HCID-A PPE, which led to protocol changes. Discussion: The transfer of an HCID-A ECMO patient is an unusual, complex and high-risk scenario and our simulation successfully tested our institution's ability to respond to this. This was facilitated by careful prior planning and engagement of the MDT. Our experience was that in situ simulation was essential in development of a safe HCID-A SOP. Our intention is to continuously re-evaluate our protocols using simulation, in order to maintain maximum safety and best practice. References: Public Health England (2018) Investigation and public health management of possible cases of Middle East respiratory syndrome coronavirus (MERS-CoV)v31 Patterson M, et al. In Situ Simulation: Challenges and Results. In: Henriksen, et al. Advances in Patient Safety: New Directions and Alternative Approaches (Volume 3: Performance and Tools). Rockville, 2008